Device physics and device integration of two-dimensional heterostructures - Kumar C.; Das S.; Jit S. (My University, 2025)
Heterostructures are widely used as a basic building block in the advanced semiconductor devices owing to their essential and attractive structural, interfacial, and electronic properties. In general, heterostructures have a comparatively better electrical and optical performance with respect to the layers of individual materials. The charge transport mechanism in the heterostructures depends on various parameters such as materials used, their band alignments, surface behavior, interfacial characteristics, the mobility of charge carriers, etc. Recently, the nanomaterials, especially two-dimensional (2D) materials based 2D heterostructures have attracted various optoelectronics applications due to their unique and interesting properties. In this context, the current chapter presents the developments in the 2D materials-based heterostructures and the physics of device based on 2D heterostructure materials. Depending on charge conduction and bandgap, 2D materials are categorized in semimetal, semiconductor, and insulator. Thus the 2D heterostructures are formed in a variety of combination, namely semimetal/semiconductor, semimetal/insulator, semiconductor/semiconductor, semiconductor/insulator, and several others. The characteristics of these different type of heterostructures have shown that the 2D heterostructure needs their device physics different from convention semiconductor device physics. This chapter elaborates the different 2D heterostructures along with their structural, physical, and electronic properties and the fundamental understanding of those 2D heterostructure based electronic devices. © 2020 Elsevier Inc.